Transcription Factor Control of Lymphatic Quiescence and Maturation of Lymphatic Neovessels in Development and Physiology - Tabrizi, Zarah B.; Ahmed, Nada S.; Horder, Joseph L.; Storr, Sarah J.; Benest, Andrew V. (Frontiers in Physiology, 2021)
The lymphatic system is a vascular system comprised of highly specialised lymphatic endothelial cells. The system has diverse functions in both physiology and pathology. It has become increasingly evident that remodelling of the lymphatic system occurs alongside remodelling of the blood microvascular system, which is now considered a hallmark of most pathological conditions. Much attention has focussed on how the blood endothelium undergoes phenotypic switching in development and disease, resulting in nearly two decades of research to probe the mechanisms underlying the resulting heterogeneity. The lymphatic system has received less attention, and consequently there are fewer descriptions of functional and molecular heterogeneity, but it is clear that differential transcription factor activity is likely an important avenue to identify such diversity. Here we introduce and discuss likely transcription factors of relevance to coordinating cellular responses during lymphatic remodelling.